Enhancing student satisfaction through open collaborative practical teaching reforms in public health education: a comparative study - Tiantian Zhao; Wenhang Deng; Yadi Yang; Yuyang Jin; Fang Xu (Frontiers in Public Health)
BackgroundPractical teaching is vital for preparing public health students to address real-world challenges. This study evaluates the impact of open collaborative practical teaching reforms on student satisfaction compared to traditional approaches.MethodsA validated Likert scale-based questionnaire assessed satisfaction among 188 public health students (96 Reform Group; 92 Traditional Group). Reliability (Cronbach's α = 0.987) and validity (KMO = 0.948; p < 0.001) tests confirmed the instrument's robustness. Comparative analyses examined satisfaction across teaching methods, course content, and teaching effectiveness.ResultsThe Reform Group reported significantly higher satisfaction, particularly in Health Statistics, Instrumental Analysis, and Water Quality Inspection courses. Reforms enhanced student engagement, teaching methods, and collaboration between universities and public health institutions.ConclusionsThis study demonstrates the effectiveness of open collaborative teaching reforms in improving public health education, emphasizing their potential to foster innovation and align education with modern public health demands.